Effects of Sex, Gender Stereotypes and Gender Identity in Male and Female Students’ Reading Motivation - Espinoza, Ana María; Strasser, Katherine; Carvacho, Héctor (Psykhe, 2024)
This study aimed to enhance our understanding of the biological sex gap in the reading motivation of students by focusing on the role of gender variables. 303 Chilean secondary students (51% female) completed self-report questionnaires. Structural equation models were employed to assess whether gender identity mediated the relationship between biological sex and reading motivation (reading self-concept and value) and to examine the differential effects of gender identity and reading-gender stereotypes on the reading motivation of male and female students. The results indicated direct effects of biological sex but no indirect effects. Multi-group analysis revealed that for female students, adherence to reading-gender stereotypes positively influenced reading self-concept, whereas for males, it negatively affected reading value. Implications for promoting equity in the teaching and learning of reading in secondary education are discussed.